Facing or Retreating? Evaluating The Impact of Corruption, Financial Access, and Gender on Corporate Tax Compliance - Safira Ainun Nisa; Dwi Sintia Wati; Ahmad Syifaudin (Journal Research of Social Science, Economics, and Management, 2024)
This study investigates how corruption, financial access, and gender affect tax compliance. 52 nations' worth of World Bank Survey data from 2019 to 2023 are used in this analysis. This investigation's results demonstrate that corruption positively impacts tax compliance. The second conclusion is that money availability improves tax compliance. The conclusion is that tax compliance has no benefit from having female senior managers. The keys to increasing tax compliance are avoiding dishonest behavior, paying taxes cooperatively, and allowing businesses to obtain financing. Our study incorporates the gender of firm managers, access to financing, and corruption into a model to forecast how enterprises will comply.